Crooked nose-extracorporeal septoplasty to the rescue: case report - Munjal, Manish; Munjal, Shubham; Talwar, Shivam; Chawla, Deeksha; Kaur, Hardeep; Sandhu, Loveleen; Arora, Anurima; Bharadwaj, Iti; ., Abhiroop; Chahal, Jasmeen; Gill, Zoya; Joshi, Tanvi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
The nasal dorsum necessitates intervention at the level of its underlying septal support, in marked deformities, to achieve an acceptable outcome. Conventional intranasal septal access gives limited correction in severe deviations and often an extracorporeal approach is required. This technique, improves the individual’s nasal airway as well as the nasal aesthetics, even in the most advanced deformities. The extracorporeal procedure was undertaken in a robust gentleman with a gross internal and external deformity with a satisfactory result.